Assessing the Millennials’ Intention Toward Green Fast Food Retail: The Use of the Theory of Planned Behavior - Hayuningardi, Bella Marhaenia Dyah Ayu Pithaloka; Najib, Moh Farid; Purnamasari, Yessy (Journal of Marketing Innovation (JMI), 2024)
The existence of this interest can indirectly affect the existence of fast-food retail because of negative consumer perceptions related to fast-food retail. Therefore, several fast-food retailers have offered eco-friendly products, in great demand by Millennials. However, it is still rare for fast-food retailers to launch new outlets with green themes due to the adverse insight of fast food itself. It is also caused by data deficiency on consumer behavior intention towards green fast-food retail, even though the existence of this restaurant itself continues to increase, especially in West Java. Therefore, this study aims to examine the intention of millennial consumers in West Java’s green fast-food retail by applying the Theory-of-Planned-Behavior approach with the role of green knowledge, perceived green practices, perceived physical servicescape, and perceived price fairness. 402 respondents were gathered in this study by implementing TPB theory as the variable under study, supported by Green Knowledge, Perceived Green Practices, Perceived Physical Servicescape, and Perceived Price Fairness. A quantitative approach is employed and processed using SPSS and Smart-PLS. Based on the results, the company's green practices, physical service scape, and price fairness affect consumer behavior control which leads to a positive influence on consumer behavior intention in green fast-food retail. Another result proved that green knowledge has a positive and significant impact on consumer attitude